A PARADIGM SHIFT WELLBEING METHODOLOGY IN SOCIAL AND HUMANITIES RESEARCH - Suriadi, Jadi Suriadi (University of Darussalam Gontor Press, 2023)
This research delves into the intricate aspects of methodology, presenting a series of procedural steps utilized in empirical research titled